Large‐scale field testing of geotechnical seismic isolation of structures using gravel‐rubber mixtures - Pitilakis, Dimitris; Anastasiadis, Anastasios; Vratsikidis, Athanasios; Kapouniaris, Anastasios; Massimino, Maria Rossella; Abate, Glenda; Corsico, Sebastiano (Earthquake engineering & structural dynamics, 2021)
We present the results of a large‐scale experimental campaign performed on the prototype structure of EuroProteas in Thessaloniki, Greece, to assess the effectiveness of gravel‐rubber mixture (GRM) layers underneath shallow foundations as a means of geotechnical seismic isolation (GSI). We found that the GSI of structures is optimized by increasing the rubber content of the soil‐rubber mixture up to 30% per mixture weight. The effectiveness of the GSI systems has been investigated numerically and in small‐scale experiments. This article seeks to fill the gap in the lack of full‐scale experimental studies on this subject. Three soil pits were excavated and backfilled with GRM of different rubber content per weight to serve as foundation soil. A large number of instruments were installed on the structure, the foundation, the soil surface, and inside the GRM layers beneath the foundation to fully monitor the GSI‐structure systems’ response in three dimensions. The experimental investigation included ambient noise, free‐ and forced‐vibration tests. Our results showed that a GSI layer composed of a GRM with 30% rubber content effectively isolates the structure. Even 0.5 m thickness (ie, B/6 of the foundation width) of the GSI system successfully cuts off practically all emitted waves at a (horizontal or vertical) distance of B/6 from the foundation. A significant reduction in the GSI‐structure system's stiffness was apparent, leading to a rocking‐dominant response. The rise in the system's damping and the substantial energy dissipation inside the GRM layer highlight its effectiveness as a GSI system.